Public Perception of PATI ( Pendatang Asing Tanpa Izin ) Policy : An Exploratory Study in Kota Kinabalu / Carlneno Jison ... [ et al. ] - Jison, Carlneno; Tuyun, Roslan (2012)
The state government approaches to solve illegal immigrant problem in Sabah is keep changing since USNO era. It keeps changing until BN took over the state government in Sabah. Open-door policy and accommodating is the approach that USNO government used towards PATI issue in Sabah. BN applied the Closed-door policy and non- accommodating and until nowadays there is no consistencies on government policy towards combating PATI. Amnesty program, special task force and RCI was implemented however the result is still not as expected. Policies inconsistencies implementation in Sabah makes people now opening their mind toward the implementation of the policies. This research will discuss about the people's perception towards policy implementation in combating the PATI issue. It is the main objective of this study. Among the issue that discussed in this research are correlation between the level of education and their perception and the relationship between age and the perception. Illegal immigrant becomes the threat to local people. Thus, it can be identify whether it is true or not through this exploratory study. Judgmental sampling is the method that been used in this study. The result of the study was people have negative perception towards policies that has been implemented in order to combating PATI issue. That mean policies that has been implemented is not successfully solving the PATI issue. Government has to be more consistent in order to solving PATI issues through the comprehensives policies so that the PATI issue can be resolve for Sabahan future.